2011
DOI: 10.1121/1.3569726
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of standing-wave errors in real-ear sound-level measurements

Abstract: Standing waves can cause measurement errors when sound-pressure level (SPL) measurements are performed in a closed ear canal, e.g., during probe-microphone system calibration for distortionproduct otoacoustic emission (DPOAE) testing. Alternative calibration methods, such as forwardpressure level (FPL), minimize the influence of standing waves by calculating the forward-going sound waves separate from the reflections that cause errors. Previous research compared test performance (Burke et al., 2010) and thresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…These findings indicate that a lack of standing-wave effects on SPL calibration could not account for the general lack of improvements seen with FPL calibration. Additionally, Richmond et al (2011) demonstrated that improvements in test performance at 8 kHz could not be attributed to detrimental standing-wave effects on SPL calibration at that frequency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicate that a lack of standing-wave effects on SPL calibration could not account for the general lack of improvements seen with FPL calibration. Additionally, Richmond et al (2011) demonstrated that improvements in test performance at 8 kHz could not be attributed to detrimental standing-wave effects on SPL calibration at that frequency.…”
Section: Introductionmentioning
confidence: 99%
“…However, Richmond et al (2011) re-examined the data and found the strongest evidence of standing-wave nulls at 4 kHz across subjects. These findings indicate that a lack of standing-wave effects on SPL calibration could not account for the general lack of improvements seen with FPL calibration.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that the rms error at 4 kHz is usually higher than the error at 1 and 2 kHz. The source of the error may be related to standing-wave errors which have been shown to occur near this frequency (e.g., Scheperle et al, 2008;Richmond et al, 2011).…”
Section: Fig 6 (Color Online)mentioning
confidence: 99%
“…Although recent data suggest that DPOAE test performance or predictions of threshold are not affected by calibration Rogers et al, 2010), concerns have been noted for potential errors associated with standing waves when using the present calibration method (Siegel, 2002(Siegel, , 2007Scheperle et al, 2008;Kirby et al, 2011). Therefore, it is possible that using either sound intensity level or forward pressure level during calibration may have reduced calibration errors Scheperle et al, 2008;Kirby et al, 2011;Richmond et al, 2011) and resulted in greater reliability.…”
Section: Discussionmentioning
confidence: 93%